Qualitative or Quantitative Data for Nuclear Control Room Usability Studies? A Pragmatic Approach to Data Collection and Presentation. (September 2018) - Ulrich, Thomas A.; Boring, Ronald L.; Lew, Roger
Qualitative and quantitative approaches provide alternative, but often incompatible means to answer design questions during the early formative and later summative evaluation phases of the human-system interface design process. Human factors practitioners and researchers should identify which approach best addresses their particular research needs. Nuclear control room studies, particularly those conducted for control room modernization efforts, pose unique challenges. Due to the challenge of sampling large numbers of operators, the interface improvement goals of a usability evaluation, and the limited resources available for study analyses, a traditional quantitative approach is often not feasible or reasonable. Qualitative data provides a more pragmatic means to address design questions early on during the formative stage of the evaluation. Quantitative data can also be useful to bolster the qualitative data by presenting the data in a simple and intuitive graphic to provide evidence for design choices. An example case study using this approach during a formative evaluation study of a turbine control system human-system interface is described in this paper.